The equation is -3x+2y=12
To find the y intercept, we simply let x equal 0.
So -3(0)+2y=12
or y=6, this is the y intercept.
The point is (0,6)
You can also write the original equation as
2y=3x+12 or y=3/2x +6 which tells you write away the
y intercept is 6 since this is slope intercept form (y=mx+b) where b is the slope.
Now to find the x intercept, let y=0
So you have 0=3/2x+6 or
-6=3/2x ro -12=3x and the x intercept is -4.
It is probably easier to set y=o in the original equation
so we have -3x+0=12 and x=-4 again so the point is (-4,0)
x+2y = 2 2y = -x+2 y = -0.5x+1 Therefore the slope is -0.5 and the y intercept is 1
2y - 4x = -12 Algebraically rearrange to 2y = 4x - 12 Divide both sides by '2' y = 2x - 6 So at the 'y' intercept, x = 0 Substituting x = 0 We have y = 2(0) - 6 Anything multiplied '0' is equal; to '0' Hence y = 0 - 6 y = -6 is the value of the y-intercept.
If you mean: 2y = -4x-12 then y = -2x-6 and -6 is the y intercept
3x+2y-5=0 3x+2y=5 Im lost im only 12 work out the rest hope i helped
Put in this form.......Y = mX + bb = Y intercept.3X - 2Y = 6- 2Y = - 3X + 6Y = (3/2)X - 3================
If: -3x+2y = 12 Then: y = 1.5x+6 in slope-intercept form
4x+2y = 12 2y = -4x+12 y = -2x+6 So the y intercept is 6 and the slope is -2
(0,6)
2x-y=4
It is a straight line equation that can be rearranged into slope intercept form: -x+2y = 12 2y = x+12 y = 0.5x+6 which is now in slope intercept form
For 4x + 2y = 6The X intercept is 1.5The Y intercept is 3
the x intercept is 3
7x = -3y + 12
4x-2y = 12 -2y = -4x+12 y = 2x-6 Therefore the y intercept is -6 and the slope is 2
-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6
-6
3x - 2y = 12 2y + 12 = 3x 2y = 3x - 12 y = 3x/2 - 6 Gradient = 3/2 Y-intercept = -6